Perancangan Produk Aksesoris Fashion dengan Pemanfaatan Limbah HDPE dan PPE - Litania, Andrea Valerie; Sugianto, Donna Angelina (Desainpedia: Jurnal Desain Produk dan Desain Komunikasi Visual, 2024)
Plastic is the most frequently used material as a storage container by the public. Its various purposes, wide range of colors, types, and sizes, its versatility makes plastic a popular choice of material. One of the characteristics of plastic is its single-use, which implies it often being thrown away after one use and increases the amount of plastic waste in circulation. One of the most frequently found plastic wastes in circulation is HDPE plastic, which has become a pollutant that contaminates both land and bodies of water. Management of plastic waste is currently still ineffective, that eventually end up in landfills or burned. HDPE plastic waste can be processed and repurposed into a new product to produce jewelry designs. HDPE plastic that will be processed will undergo a meticulous and attentive process to ensure its quality and cleanliness, so it can remain safe when it has direct contact to human skin. Plastic that is one of the biggest pollutants in the world, can be repurposed and produced as a new product that can be used every day, to reduce the number of plastic pollutants.